The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
All Days 2005
DOI: 10.2118/93765-ms
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks Models for Predicting PVT Properties of Oil Field Brines

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractKnowledge of chemical and physical properties of formation water is very important in various reservoir engineering computations especially in water flooding and production. Ideally, those data should be obtained experimentally. On some occasions, these data are not either available or reliable; then, empirically derived correlations are used to predict brine PVT properties. These correlations offer a handy and an acceptable approximation of formation water p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The recent success of applying artificial neural networks (ANN) to solve various engineering problems has drawn the attention to its potential applications in the petroleum industry. This has been recently demonstrated by several investigators in the prediction of various pressure volume-temperature (PVT) properties, e.g., Osman et al [10], AI-Marhoun and Osman [1], Osman and Al Marhoun [11], and more recently, Elshafei and Hamada [4], and Oloso et al [9]. It was observed that ANN models have superior performance and accuracy in performing predictions compared to those of the available correlations.…”
Section: Introductionmentioning
confidence: 93%
“…The recent success of applying artificial neural networks (ANN) to solve various engineering problems has drawn the attention to its potential applications in the petroleum industry. This has been recently demonstrated by several investigators in the prediction of various pressure volume-temperature (PVT) properties, e.g., Osman et al [10], AI-Marhoun and Osman [1], Osman and Al Marhoun [11], and more recently, Elshafei and Hamada [4], and Oloso et al [9]. It was observed that ANN models have superior performance and accuracy in performing predictions compared to those of the available correlations.…”
Section: Introductionmentioning
confidence: 93%
“…Examination of the model including all fluids type revealed a lower level of error compared to tuned equation of state models. Osman and AlMarhoun (Osman and Al-Marhoun, 2005) applied radial basis functions and multilayer perceptron neural networks and developed two intelligent models to predict oil field brines PVT properties. In 2009, Khoukhi et al (Khoukhi et al, 2011) published predictive models based on three different artificial intelligent models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The CI techniques achieved this by establishing nonlinear relations between the log measurements and the core values for prediction. CI techniques have also been reported to outperform the statistical regression tools (Mohaghegh 2000;Goda et al 2003;Osman and Al-Marhoun 2005;Zahedi et al 2009;Al-Marhoun et al 2012).…”
Section: Introductionmentioning
confidence: 99%